International - Correia, Larry (Riverdale, NY New York, NY Baen Publishing Enterprises Distributed by Simon & Schuster, 2009)
"Five days after Owen Zastava Pitt pushed his insufferable boss out of a fourteenth story window, he woke up in the hospital with a scarred face, an unbelievable memory, and a job offer. It turns out that monsters are real. All the things from myth, legend, and B-movies are out there, waiting in the shadows. Officially secret, some of them are evil, and some are just hungry. On the other side are the people who kill monsters for a living. Monster Hunter International is the premier eradication company in the business. And now Owen is their newest recruit. Business is good ... Welcome to Monster Hunter International."--Page 4 of cover
"Baen Science fiction"--Spine
113821
Keywords: Monsters -- Fiction; Animals, Mythical -- Fiction; Paranormal fiction; Fantasy fiction; Horror fiction; Fiction